2010
DOI: 10.1002/etc.302
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new toxic‐unit model for the bioassessment of metals in streams

Abstract: Two toxic-unit models that estimate the toxicity of trace-metal mixtures to benthic communities were compared. The chronic criterion accumulation ratio (CCAR), a modification of biotic ligand model (BLM) outputs for use as a toxic-unit model, accounts for the modifying and competitive influences of major cations (Ca²(+), Mg²(+), Na(+), K(+), H(+)), anions (HCO₃⁻, CO²⁻₃ ,SO²⁻₄, Cl⁻, S²⁻) and dissolved organic carbon (DOC) in determining the free metal ion available for accumulation on the biotic ligand. The cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 33 publications
5
95
1
Order By: Relevance
“…Despite the applications of several ecotoxicological models to predict the acute effects of multiple metals in the laboratory [43], no model is available that can quantitatively evaluate the effects of multiple metals in natural systems. More recently, a few mechanically based models have been proposed and applied to riverine macroinvertebrate data [27,28] but they have not been fully validated. For instance, Schmidt et al [27] used the outputs of a biotic ligand model [32] to evaluate the effects of metals in natural streams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the applications of several ecotoxicological models to predict the acute effects of multiple metals in the laboratory [43], no model is available that can quantitatively evaluate the effects of multiple metals in natural systems. More recently, a few mechanically based models have been proposed and applied to riverine macroinvertebrate data [27,28] but they have not been fully validated. For instance, Schmidt et al [27] used the outputs of a biotic ligand model [32] to evaluate the effects of metals in natural streams.…”
Section: Discussionmentioning
confidence: 99%
“…We used two types of piecewise regression in which the slope of the left line in the model was zero (no effect below a certain concentration) or not zero (some effect). Although some other nonlinear models (e.g., a model using a smooth-transition function [25]) can be applied to evaluate the threshold response, we only used the piecewise regression model in the present study because it was applied in previous studies to evaluate the effects of metals on macroinvertebrates [27][28][29]. When fitting the piecewise regression model to our data, we used several initial values for estimating the breakpoint (1, 1.5, 2, 2.5, and 3 of log 10 -transformed concentrations of Zn) in order to avoid convergence to local minima [30].…”
Section: Effects Of Zn On Riverine Macroinvertebrate Diversitymentioning
confidence: 99%
“…Recently important attempts have been proposed in order to assess field effects of metal mixtures, e.g. the Chronic Criterion Accumulation Ratio (CCAR) (Schmidt et al, 2010) and the WHAM-FTOX model ( Stockdale et al, 2010). The latter concept describes toxicity of proton-metal mixtures to aquatic invertebrates in natural streams and is based on chemical speciation using the Windermere Humic Aqueous Model (WHAM) ( Tipping, 1994 andTipping, 1998) to predict the metabolically-active metal accumulated by the organism ( Stockdale et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Critical loads have been extensively used in air pollution control in long-term monitoring programs in Europe (Long-Range Transboundary Air Pollution: http://www.unece.org/env/lrtap/) and in the United States (National Atmospheric Deposition Program: http:// nadp.isws.illinois.edu/). Sonderegger et al (2009) and Schmidt et al (2010) have also shown useful and different applications of the concept of ecological thresholds in aquatic systems by evaluating the effects of metals on macrobenthic community composition.…”
mentioning
confidence: 99%
“…Although SiZe cannot provide estimates and confidence regions for the thresholds it detects, it has shown good potential in critical thresholds evaluation. Akaike's information criterion (AIC) can be used as well for model averaging and testing by the method of maximum likelihood, taking the predictions of all reasonable models into account (e.g., Schmidt et al 2010).…”
mentioning
confidence: 99%